Superbugs Unleashed: Is Time Running Out to Stop the Global Infection Crisis? - Khumukcham Anupama Devi; Thokchom Soniya Devi; Sudhakar Kumar Singh (International Journal of Medical Research and Review, 2024)
The global infection crisis poses a significant threat to public health, with the emergence and spread of antibiotic-resistant bacteria or "superbugs" becoming a major concern. The crisis has been fueled by various factors, including overuse of antibiotics, inadequate infection prevention and control measures, and the lack of investment in research and development of new treatments. Addressing this issue requires a comprehensive approach that involves improving surveillance and monitoring systems, promoting individual responsibility, and investing in research and development. Collaboration between stakeholders, including governments, healthcare providers, researchers, and the public, is crucial in overcoming the challenges posed by the global infection crisis. Despite promising advances in emerging technologies, sustained investment in research and development is necessary to ensure continued progress in addressing the issue. Failure to take action risks a future where superbugs run rampant and existing treatments become ineffective. It is time to act decisively to halt the spread of superbugs and prevent a global health crisis.